Wet steam generation procedure influence on thermodynamic and aerodynamic processes in wet steam zone for experimental researches - Скляров, В. П. (Інститут енергетичних машин і систем ім. А. М. Підгорного Національної академії наук України, 2016)
Mechanism of wet steam generation procedure influence on investigation results on expanding wet steam in two-phase zone is considered. It is shown that wet amping by spit of water create precondition for incorrect inference and ipso facto isorientate observer